Determinantes do Cometimento de Ilicitudes na Gestão Municipal: O Caso do Ceará - Lopes Neto, Manuel de Araripe (2018)
Most of the state and federal resources transferred to the municipalities are controlled by municipalities, therefore, the mayor, as the main manager of these resources, has a high discretion in its allocation. In view of this prerogative, the Mayor, in certain cases, evidence of deviations in transfers without the consent or participation thereof will be non-existent. In order to analyze possible acts of illegalities in the prefectures of Ceará in the years 2009 to 2016, a basic econometric model of discrete choice is proposed, from which the following conclusions were drawn: 1) re-elected mayors are more likely not to have disapproved accounts; 2) audited municipalities are more likely to have disapproved accounts; 3) the variable education (supply) presented a negative signal indicating that the greater the probability of non-compliance with the RFL; 4) the variable health (supply) presented negative sign indicating that the chance of committing illicit acts decreases whenever more health is offered.